Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/vaccines10101698
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with a Prefusion SARS-CoV-2 Spike Protein Vaccine (RBMRNA-176) Protects against Viral Challenge in Mice and Nonhuman Primates

Abstract: There is an urgent need for a broad-spectrum and protective vaccine due to the emergence and rapid spreading of more contagious SARS-CoV-2 strains. We report the development of RBMRNA-176, a pseudouridine (Ψ) nucleoside-modified mRNA-LNP vaccine encoding pre-fusion stabilized trimeric SARS-CoV-2 spike protein ectodomain, and evaluate its immunogenicity and protection against virus challenge in mice and nonhuman primates. A prime-boost immunization with RBMRNA-176 at intervals of 21 days resulted in high IgG ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…The results showed that the FLUCOV-10 elicited significantly higher HA- and spike-specific interferon γ (IFN-γ) and interleukin-2 (IL-2) producing splenocytes, compared to those of placebo (Figure 3A and B), while the FLUCOV-10 did not elicit higher IL-4 and IL-5 producing splenocytes (Figure 3C and D). These results indicate that the FLUCOV-10 vaccination activates Th1-biased immune responses, aligning with the observation in our previously developed mRNA vaccine platform (11, 12).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The results showed that the FLUCOV-10 elicited significantly higher HA- and spike-specific interferon γ (IFN-γ) and interleukin-2 (IL-2) producing splenocytes, compared to those of placebo (Figure 3A and B), while the FLUCOV-10 did not elicit higher IL-4 and IL-5 producing splenocytes (Figure 3C and D). These results indicate that the FLUCOV-10 vaccination activates Th1-biased immune responses, aligning with the observation in our previously developed mRNA vaccine platform (11, 12).…”
Section: Resultssupporting
confidence: 90%
“…We dissected the protein expression and immune response induction for each component of FLUCOV-10. Similar to previous findings (11, 12), each component in FLUCOV-10 resulted in abundant expression of HA or spike proteins in cell lysates (Figure 1 D and E), leading to robust component-specific humoral responses (Figure 2) and Th1-favored cellular responses (Figure 3) following a two-dose regimen. In response to the constantly evolving and antigenically diverse strains of influenza and SARS-CoV-2, we also evaluated the cross-reactive immunity conferred by FLUCOV-10.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, early preclinical studies with these vaccines using inbred mouse strains generally showed uniform immunogenicity and protection against SARS-CoV-2 infection [ 18 , 44 , 51 , 52 , 53 ]. Although variation is observed in lower vaccine doses (<1 µg), mouse studies analyzing neutralizing response in inbred strains with protein vaccination and similar adjuvants have little variation in neutralizing antibody titers [ 54 , 55 , 56 ].Therefore, one of our goals was to determine whether the DO mice would more accurately reflect the variation in vaccine immunogenicity and efficacy seen in human populations. This was borne out in our studies, where the DO mice showed over 100-fold variation in the magnitude of vaccine-induced neutralizing antibody responses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, balancing and regulating the response of the immune system, in order to ensure that the vaccine does not trigger inappropriate inflammation or autoimmune damage when inducing immunity, are key issues in the application of mRNA vaccines. In addition, the versatility of mRNA vaccines across different tumor types and individuals is also a challenge [ 92 , 93 , 94 , 95 ]. Due to tumor heterogeneity and individual patient differences, it is difficult for a single mRNA vaccine to cover all tumor types.…”
Section: Mrna Vaccines and Tumor Immunitymentioning
confidence: 99%